Advances in molecular characterization of pediatric acute megakaryoblastic leukemia not associated with Down syndrome; impact on therapy development - Li, Jixia; Kalev‐Zylinska, Maggie L. (Frontiers in Cell and Developmental Biology, 2023)
Acute megakaryoblastic leukemia (AMKL) is a rare subtype of acute myeloid leukemia (AML) in which leukemic blasts have megakaryocytic features. AMKL makes up 4-15% of newly diagnosed pediatric AML, typically affecting young children (less than 2 years old). AMKL associated with Down syndrome (DS) shows GATA1 mutations and has a favorable prognosis. In contrast, AMKL in children without DS is often associated with recurrent and mutually exclusive chimeric fusion genes and has an unfavorable prognosis. This review mainly summarizes the unique features of pediatric non-DS AMKL and highlights the development of novel therapies for high-risk cases. Due to the rarity of pediatric AMKL, large-scale multi-center studies are desperately needed to progress the molecular characterization of this disease and to help uncover new therapeutic targets. Better disease models are also required to test leukemogenic mechanisms and the effectiveness of experimental therapies.